Oxford Energy Forum, Issue 97 - Bassam Fattouh; James Henderson; Simon Pirani (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2014)
Energy in Russia, the subject of this issue of the Oxford Energy Forum, has this year returned to the forefront of debates among academics, policy makers, and those in the industry. Politics, never far from these debates, is a factor: as a result of events in Ukraine, the tension between Russia and the western powers has risen to its highest level since the Cold War. The editors have endeavoured to provide commentary on the political and economic context of energy developments, while also inviting recognized specialists to comment on the host of issues – from long-term upstream oil issues to Russia's domestic electricity market – that are sometimes neglected by the big-picture analysts.
Keywords: 330